Tingkat Keterampilan Sosial Siswa Kelas 7 SMP Negeri 15 Yogyakarta Tahun Ajaran 2023/2024 - Anastasia Febriana Swastono; A. Setyandari (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
This study aims to determine the level of social skills of 7th grade students of SMP Negeri 15 Yogyakarta in the 2023/2024 school year and to find out the low items to be proposed as guidance topics. This type of research is descriptive quantitative with the subjects in this study are 7th grade students in the 2023/2024 school year. Determination of the sample from the population was carried out using calculations made by Issac and Michel with an error of 10%. Data collection was carried out using a social skills scale with 46 valid items with a Cronbach alpha reliability index of 0.945 which is in the very strong category. The scale is arranged based on 5 (five) aspects, namely cooperation, assertiveness, responsibility, empathy, and self-control. The data analysis technique used descriptive statistics, using the SPSS Ver. 25. With the results, most of the 7th grade students of SMP Negeri 15 Yogyakarta in the 2023/2024 school year have high social skills. The results showed that in 166 students, 35% of students had a very high level of social skills, 55% of students had a high level of social skills, and 10% of students had a moderate level of social skills. There are no low items on the social skills scale that will be proposed as guidance topics.